Intergenerational transmission of educational attainment: Three levels of parent–child communication as mediators. Issue 1 (27th December 2012) - Chi, Liping
Abstract Although the intergenerational transmission of educational attainment has been confirmed by many researchers, its mechanism still remains controversial. Parent–child communication has been regarded as one of the important mediators. The present study primarily aimed to examine the potentially mediating role of parent–child communication in the transmission of educational attainment, based on a sample of 366 Chinese fifth and sixth graders. Parent–child communication was measured against the three levels of the parents' communication ability, the quality of the father–child and mother–child communications, and the relation between the two dyadic communications. The results duplicated the positive effect of parents' educational attainment on children's academic achievement. Moreover, it was found that parents' communication ability alone played a mediating role, and that the three levels of parent–child communication constructed a "mediator chain" between the parents' educational attainment and the children's academic achievement. Finally, the intergenerational transmission of educational attainment in China and the mediating role of the three levels of parent–child communication were discussed.